The biology of Canadian weeds. 98 Potentilla anserina L. - Miyanishi, K.; Eriksson, O.; Wein, R. W. (Canadian Journal of Plant Science, 1991)
Potentilla anserina L., silverweed (Rosaceae), occurs in all provinces of Canada as well as in the two territories. Although generally found in wet sandy areas along rivers and on beaches, silverweed also occurs in waste areas, along roadsides, and in lawns. This shade-intolerant stoloniferous plant has recently become dominant in overgrazed sedge meadows of the Peace-Athabasca Delta, resulting in deterioration of portions of the primary range for wood bison in Wood Buffalo National Park in northern Alberta. This contribution presents both a review of the literature and some original data on the biology and ecology of the species. Key words: Silverweed, disturbance, ecology, herbaceous perennial, demography